Assessment & intervention in social work - Beckett, Chris (Sage, 2010)
This book is essential reading for undergraduate and graduate social work students throughout all three years of their training, but it will be particularly useful for students who are on placement, or who are reflecting on their experiences on placement. It is also a useful resource for practice teachers who need a framework for discussing practice with students they supervise on placement; Includes bibliographical references (p. [152]-157) and index; CX032 An sinh xã hội ; CX052 Công tác xã hội trong lĩnh vực pháp luật và tội phạm